FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KUALITAS PEMERIKSAAN KEUANGAN (Studi Empiris pada Pemeriksa BPK RI Perwakilan Provinsi Kepulauan Riau) - Fransiskus Purna Adi; Sudarno Sudarno (Diponegoro Journal of Accounting, 2016)
Many factors can affect the quality of the audit. This study aims to determine the effect of experience, continuing professional education, Independence, integrity, and professionalism towards the audit quality of the Audit Board of the Republic of Indonesia. The study used primary data derived from respondents who are auditors on the Audit Board of Indonesia Representative of Provinsi Kepulauan Riau. This study used six variables. Five variables are independent variables consisting of experience, continuing professional education, independence, integrity, and professionalism, and one dependent variable is the quality of the audit. The data were analyzed using multiple linear regression test. The results showed that experience, continuing professional education, independence, integrity, and professionalism effect on audit quality simultaneously. But partially only integrity have positive effect on audit quality.